NEUROFILAMENTS AS A POTENTIAL BIOMARKER IN PATIENTS WITH MULTIPLE SCLEROSIS: A REVIEW OF LITERATURE - Magdalina Yanakieva; Maya Danovska; Emilia Ovcharova; Diana Marinova (Peytchinski Publishing, 2024)
Background: Multiple sclerosis (MS) is a chronic inflammatory neurodegenerative disease of the central nervous system (CNS) characterized by demyelination, axonal damage and loss of neurons. Its growing incidence has determined the need for more intensive research towards effective models for managing disease progression and evaluation of treatment response. Finding clinically relevant biomarkers has been a significant challenge. Purpose: This review aims to summarize the findings from current relevant literature sources on neurofilaments as a potential biomarker of diagnostic and prognostic value in patients with MS. Results: Recently, neurofilaments have been identified as the most promising and informative biomarkers of axonal damage and loss. Neurofilament concentration demonstrates a strong association with the disease course, activity and progression, disability accumulation and response to disease-modifying treatment. A significant correlation with future relapse rates, symptom worsening and risk of conversion from clinically isolated syndrome (CIS) to definite MS has also been established. Several MS therapies have demonstrated a substantial reduction in neurofilament levels upon treatment initiation. Conclusion: The results available from real-world studies and clinical trials regarding neurofilaments as a reliable predictor and indicator of MS disease course are encouraging. They have consistently proven to be of utility if integrated into the diagnostic and therapeutic algorithm of MS patients. This review encompasses undeniable data confirming the considerable potential of neurofilaments for becoming the first globally verified biomarker for MS. The accessibility, safety, low cost and possibility for serial evaluation make the neurofilaments the perfect component to be implemented in routine clinical tests for MS.